POLITICS AND POWER: A CRITICAL PERSPECTIVE ON LEGITIMACY - Derwin Tambunan (Journal of Social Political Sciences, 2021)
We know from research into politics and power that these two variables are widely discussed as interrelated concepts. However, what remains poorly understood is that politics is not only interrelated with the concept of power, but politics itself is about how power is exercised legitimately. This research aims to ascertain whether politics can be reduced to power and, if so, what precisely the concept of power can explain the essence of politics. A literature study was deployed in order to answer these questions. The findings showed that power is the essence of politics; politics are enterprises sharing and shaping power. However, politics can be adequately understood if power is viewed as a legitimate capacity to act. Approaching politics outside of this definition cannot be said as a proper definition of politics because legitimacy is the heart and essential to power, and only by applying this definition politics can be adequately interpreted. If politics is seen as a right to govern and power is understood as the legitimate capacity to act, thus, these two elements will create a political obligation that is vital in a political concept. Consent and legitimacy are the two aspects necessary to achieve the right to exercise governments' political authority. If power is exercised legitimately, then it will draw people trust. People trust is the precondition in political concepts and political legitimacy, which indicates the rightfulness to govern conferred by people to political regimes or political sovereignty established in the collective advantage or common good.